RESPONSE OF GRAFTS OF DIFFERENT SCION VARIETIES ON DIFFERENT ROOTSTOCK OF MANGO (MANGIFERA INDICA L.) UNDER NURSERY CONDITIONS - KIRAN, S; IQBAL, J; BIBI, F; KHADIJA, F; AZIZ, S; RASHID, MZ; AMINA, .; ULLAH, I; JAVAAD, HW (Biological and Clinical Sciences Research Journal, 2024)
An investigation was carried out at the Mango Research Station in Shujabad, Pakistan, to assess the efficacy of different scion kinds on various rootstocks of mango (Mangifera indica L.) in a nursery setting. The study comprised of thirty-six treatments, which consisted of twelve different rootstocks (Chaunsa, Langra, Anwar Ratol, Dusheri, Sindhri, Beganapalli, Malda, Fazli, Gulab Khas, Alphonso, Lal Baug, and Local) and three scion kinds (Sindhri, Chaunsa, and Langra). Anwar Ratol demonstrated the quickest germination period, the longest length of sprout, the highest rate of successful grafting, the tallest height of the grafted plant, and the greatest number of leaves per graft. These figures were recorded as 13.47 days, 7.08 cm, 92.17%, 30.4 cm, and 19.33 leaves, respectively. The Fazli rootstock exhibited the greatest scion girth and root-collar diameter, measuring 5.87 mm and 6.77 mm, respectively. Chaunsa, a type of scion, exhibited the fastest sprout emergence time (16.92 days), the greatest sprout length (6.39 cm), a high success rate of grafting (88.83%), a tall height of the grafted plant (27.74 cm), a scion girth of 5.75 mm, and a root-collar diameter of 6.61 mm. The grafting of Chaunsa scion onto Anwar Ratol rootstock resulted in the shortest sprouting time (12.4 days), the longest sprout length (8.15 cm), the best success rate of grafting (97%), the tallest grafted plant (34.55 cm), and the greatest number of leaves per graft (20.7). There were no significant variations seen in the scion girth and root-collar diameter in this particular combination